The influence of the diet on somatic differences and the developed power of athletes training strength sports - Mizera, Krzysztof (Journal of Education, Health and Sport, 2022)
Introduction: For strength training to be effective, proper nutrition is necessary, based on providing the right amount of energy, as well as optimally balanced macronutrients. Nutrition among bodybuilders, weightlifters and powerlifters differs because the training aims, training methodology and competition itself are different. Objective: Strength sports athletes differ from each other in body structure, training methodology and form of competition. The aim of the study was to try to answer the question whether their diets affect somatic variables and leg power. Materials and Methods: 60 people remained, which were divided into 4 groups, including 15 weightlifting competitors, 15 powerlifters, 15 bodybuilders and 15 men not training competitive sport Results: The quality of the diet used had an impact on the body composition in the control group. In the group of powerlifters, there was a significantly positive correlation between the daily intake of carbohydrates and the percentage of body fat (p <0.05). In the group of bodybuilders, the energy value of food consumed during a week and a day as well as the mass of daily carbohydrates and their energy value significantly correlated with the BMI index. Moreover, the energy value of consumed food expressed in kcal positively correlated with the fat content in the body expressed in kg, as well as with the chest circumference during inhalation and with the circumference of the arm. The daily amount of carbohydrates and the daily energy value of this substrate positively correlated with the circumference of the arm and the thigh. In the athletes, numerous correlations between the diet used and the developed power were demonstrated. Conclusion: The diet used by the respondents did not clearly affect the power developed by the respondents. Significant correlations between the quality of the diet used and somatic variables as well as the developed power were noticed only in the group of weightlifters and bodybuilders.